Cu2ZnSnSe4 Thin‐Film Solar Cells by Thermal Co‐evaporation with 11.6% Efficiency and Improved Minority Carrier Diffusion Length. Issue 7 (10th December 2014) - Lee, Yun Seog; Gershon, Talia; Gunawan, Oki; Todorov, Teodor K.; Gokmen, Tayfun; Virgus, Yudistira; Guha, Supratik
<x xml:space="preserve">Abstract</x> 11.6%‐efficiency Cu2ZnSnSe4 (CZTSe) thin‐film solar cells are fabricated via a thermal co‐evaporation method. The CZTSe thin film with improved microstructure exhibits a minority carrier diffusion length over 2 μm, resulting in efficient photogenerated carrier collection in the device. A comparative study of photoluminescence in pure selenide and pure sulfide devices shows reduced band‐tailing for the pure selenide phase. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>